2004
DOI: 10.1111/j.1601-5223.1998.t01-1-00231.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Chromosomes and Genome Organization of Thapsia Garganica L. by Localizations of rRNA Genes using Fluorescent in Situ Hybridization

Abstract: The karyotype (2n = 22) of Thapsia garganica L. (Apiaceae, Apioideae, Laserpitieae) was constructed using molecular cytogenetics. The size of the 22 chromosomes ranged between 5 and 10 microns. Two chromosomes had satellites on the short arms. The 18S-5.8S-26S rDNA genes were located to the two satellites by fluorescent in situ hybridization (FISH). The 5S rDNA repeat unit was amplified and located by FISH to one pair of the non-satellited chromosomes. Sequencing 5S rDNA of T. garganica revealed two classes of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…In this study, germination of T. garganica seeds was ameliorated by scarification with NaOCl as this was used as the decontamination agent of these seeds. On the other hand, Rasmussen and Avato (1998) imbibed seeds and treated them with gibberellic acid for 18 h in order to initiate germination of T. garganica and subsequently observed seedling emergence within 4 weeks of sowing. In the present investigation, a period of approximately 2 months was required for germination of the T. garganica seeds.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, germination of T. garganica seeds was ameliorated by scarification with NaOCl as this was used as the decontamination agent of these seeds. On the other hand, Rasmussen and Avato (1998) imbibed seeds and treated them with gibberellic acid for 18 h in order to initiate germination of T. garganica and subsequently observed seedling emergence within 4 weeks of sowing. In the present investigation, a period of approximately 2 months was required for germination of the T. garganica seeds.…”
Section: Resultsmentioning
confidence: 99%
“…The importance of T. garganica as a medicinal plant has led to an increasing number of studies focussing on the revision of the taxonomy of the genus Thapsia in order to resolve the taxonomic uncertainty surrounding this genus at present. Early studies conducted by Tutin et al (1968) identified three species within the genus Thapsia-T. garganica L., T. maxilla Miller and T. villosa L. However, recent investigations based on morphological characters (Smitt et al 1995), phytochemical analysis (Avato et al 1993;Christensen et al 1997) and the molecular characterisation of the chromosomes and genome organisation of T. garganica L. (Rasmussen and Avato 1998) have provided evidence suggesting that four species belong to this genus and that T. garganica should be considered as a separate species from T. transtagana. The major bioactive compounds synthesised by T. garganica are thapsigargin, thapsigargicin, notrilobolid and thapsivillosin (Rasmussen et al 1981).…”
Section: Introductionmentioning
confidence: 96%
“…The initial 25% of saved trees were discarded as a burn-in phase and the 50% majority-rule consensus tree and posterior probabilities (PP) of particular clades were calculated based on the remaining 60,000 trees. The effective sample size (ESS) for the estimated parameters and the convergence of the independent runs were checked using Tracer v.1.6.0 (Rambaut & al., 2014). For ML analyses, we employed the GTR + G substitution model.…”
Section: Version Of Recordmentioning
confidence: 99%
“…Although it has been described that the common distribution of petroselinic acid is of chemotaxonomic relevance, thus contributing to support a phylogenetic relathionship between closely related plant families such as for example Apiaceae and Araliaceae (Bagci 2007;Rasmussen and Avato 1998), this fatty acid is especially recognized as a high-added-value compound for its several potential industrial uses as oleochemical raw material in cosmetics, pharmaceutical or food applications (Placek 1963;Kleiman and Spencer 1982;Murphy, 2005;Sahib et al 2013;Sayed et al 2017). Attempts to genetically engineer oilseed crops with high yield of petroselinic acid to meet industrial requests have been only partially successful due the complexity of the biosynthetic pathway (Cahoon et al 1992;Cahoon and Ohlrogge 1994;Olhrogge and Browse 1995;Thelen and Ohlrogge 2002;Cahoon and Schmid, 2008), thus plants naturally producing petroselinic acid still represent the preferred source.…”
Section: Petroselinic Acidmentioning
confidence: 99%